2020
DOI: 10.1002/adma.202003598
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Enable Local and Non‐Invasive Liposome Delivery to Inflamed Skeletal Muscle and Ischemic Heart

Abstract: hampered by poor bioavailability and biostability, [3] undesirable off-target effects, [4] and obstacles presented by biological barriers, [5] thus motivating the development of drug delivery systems for efficient and localized delivery to affected tissue. Nanoparticle-based drug delivery systems for the treatment of inflammation are a powerful tool to target anti-inflammatory drugs to inflamed tissues. However, efficient local delivery remains challenging. Main hurdles include sequestration of nanoparticles b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 29 publications
3
60
0
Order By: Relevance
“…The nanoparticles neutralized proinflammatory cytokines, suppressed synovial inflammation, and alleviated joint damage in inflammatory arthritis via dampening the inflammation cascade. In one recent study, methotrexate (MTX)-loaded cationic liposome was encapsulated in neutrophil without removal of endocyte (MTX-liposome/neutrophils) for targeted delivery to inflammatory sites 92 . The oriented accumulation of MTX-liposome/neutrophils was demonstrated in both inflamed skeletal muscle and myocardial ischemia–reperfusion injury mice model, exhibiting the potential to regenerate inflamed tissue.…”
Section: Cell Membrane Vectorsmentioning
confidence: 99%
“…The nanoparticles neutralized proinflammatory cytokines, suppressed synovial inflammation, and alleviated joint damage in inflammatory arthritis via dampening the inflammation cascade. In one recent study, methotrexate (MTX)-loaded cationic liposome was encapsulated in neutrophil without removal of endocyte (MTX-liposome/neutrophils) for targeted delivery to inflammatory sites 92 . The oriented accumulation of MTX-liposome/neutrophils was demonstrated in both inflamed skeletal muscle and myocardial ischemia–reperfusion injury mice model, exhibiting the potential to regenerate inflamed tissue.…”
Section: Cell Membrane Vectorsmentioning
confidence: 99%
“…Circulating cells such as red blood cells, stem cells, and leukocytes were recently leveraged for drug delivery due to their long circulation times and tissue-homing properties in vivo [ 108 , 109 ]. A recent study by Molly M. Stevens group showed that neutrophils loaded with liposomes ex vivo could transport nanoparticles to inflamed skeletal muscle and ischemic hearts in mice, demonstrating neutrophils to be suitable carriers of nanoparticles to target an injured heart due to their inherent homing to inflammatory tissue [ 110 ]. To target migrating monocytes in circulation to mediate cardiac targeting of nanoparticles, Patrick C. H. Hsieh’s group developed a platelet-like proteoliposome (PLP) in which liposomes were incorporated with proteins isolated from platelets [ 111 ].…”
Section: Non-viral Delivery Systems Capable Of Targeting Cardiac Tissuementioning
confidence: 99%
“…Liposomes are spherical vesicles consisting of one or more phospholipid bilayers, can remarkably improve the permeability of encapsulated cargo within the target tissue, and have been widely employed for biomedical applications, such as nanomedicines and contrast agent ( Ringgaard et al, 2020 ; Che et al, 2020 ; Kim et al, 2019 ; Liu et al, 2017 ; Chen et al, 2017 ). Owing to their ideal size and excellent biocompatibility, liposomes are the promising carrier for a variety of agents, including drugs, small interference RNA (siRNA), plasmid DNA, etc.…”
Section: Introductionmentioning
confidence: 99%